PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN PERTAMBANGAN YANG TERCATAT DI BURSA EFEK INDONESIA - HASNI YUSRIANTI; YORDI RIZKI HIMAWAN (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
This study conducted aiming to assess whether there was an effect of the firm characteristics to corporate social responsibility disclosure in the mining company listed on the Stock Exchange. Characteristics of the companies used in this study are firm size, profitability, and leverage. It used the international standard ISO 26000 to assess the social responsibility disclosure.Â  The data used is secondary data which is the annual report of the mining company in 2011. The results showed that firm size and leverage has significantly effect to the disclosure of corporate social responsibility, while profitability does not has significantly effect to the disclosure of corporate social responsibility